Immune System Modulation by the Adjuvants Poly (I:C) and Montanide ISA 720 - Marques, Rodolfo F.; de Melo, Filipe Menegatti; Novais, Janaina Tenório; Soares, Irene S.; Bargieri, Daniel Youssef; Gimenez, Alba Marina (Frontiers in Immunology, 2022)
Adjuvants are essential for vaccine development, especially subunit-based vaccines such as those containing recombinant proteins. Increasing the knowledge of the immune response mechanisms generated by adjuvants should facilitate the formulation of vaccines in the future. The present work describes the immune phenotypes induced by Poly (I:C) and Montanide ISA 720 in the context of mice immunization with a recombinant protein based on the Plasmodium vivax circumsporozoite protein (PvCSP) sequence. Mice immunized with the recombinant protein plus Montanide ISA 720 showed an overall more robust humoral response, inducing antibodies with greater avidity to the antigen. A general trend for Th1/inflammatory cytokine profile was increased in Montanide-adjuvanted mice, while a balanced/regulatory profile was observed in Poly (I:C)-adjuvanted mice. Montanide ISA 720 induced a gene signature in B lymphocytes characteristic of heme biosynthesis, suggesting increased differentiation to Plasma Cells. On the other hand, Poly (I:C) provoked more perturbations in T cell transcriptome. These results extend the understanding of the modulation of specific immune responses induced by different classes of adjuvants, and could support the optimization of subunit-based vaccines.